Butterfly Wings across the Sky: Storytellers Blue Propellers Cascades in the Air—Humbly Humming Sadly Singing - Jernsletten, Kikki (Nordlit, 2004)
storytellers blue propellers cascades in the airhumbly humming sadly singingwishing you would hearthem astheygo!
Keywords: dikt; poem; butterflies; border poetics